Long term outcomes of infants born by mothers with thyroid dysfunction during pregnancy. - Lucaccioni, Laura; Ficara, Monica; Cenciarelli, Valentina; Berardi, Alberto; Predieri, Barbara; Iughetti, Lorenzo (Acta Biomedica Atenei Parmensis, 2020)
According to Barker’s hypothesis, sub-optimal conditions during gestation might affect the predisposition for diseases in adulthood. Alteration in endocrine functions during pregnancy, such us thyroid function or glucose metabolism, are not exempt. It is well known that subclinical hypothyroidism and thyroperoxidase antibodies-positive euthyroidism during early pregnancy are associated with increased risk of gestational diabetes mellitus and both conditions influence pregnancy outcome and newborn development and metabolism at short and long terms.Fetal production of thyroid hormones starts from the 12th week of gestational age. The transplacental passage of maternal thyroxine (T4) is therefore essential for the fetal neurological development, especially during the first half of pregnancy.  If this passage is interrupted, such as in premature birth, neonates are more susceptible to develop impaired thyroid function, because of physiological immaturity of their hypothalamic-pituitary-thyroid axis, acute illnesses and stressful events (sepsis, invasive procedures, drugs). The aim of this review is to investigate the short and long term effects of maternal dysthyroidisms on term and preterm newborns, with particular attention to the metabolic and thyroid consequences. Metabolic syndrome, higher body mass index and greater waist circumference, seem to be more prevalent in children of TPO-Ab-positive mothers. Maternal hypothyroidism may be associated with higher risk of gestational diabetes and adverse birth outcomes, such as preeclampsia, preterm delivery, fetal death and low birth weight offspring.  In adulthood, preterm (< 37 weeks of gestational age) or low birth weight (